Pendampingan Produk Es Krim dan Egg Roll kepada Kelompok Masyarakat Desa Warembungan, Minahasa: Mentoring on Ice Cream and Egg Roll Products for the Community Group in Warembungan Village, Minahasa (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
Warembungan Village is one of the villages in Minahasa Regency whose majority population is farmers. Warembungan Village has three (3) elementary schools. Currently, partners need assistance to be able to implement nutritious food for children. The existing situation analysis shows that there are several tourist attractions in Warembungan Village that provide opportunities for community groups to prepare nutritious food. The solutions offered to Warembungan Village community partners are assistance in making egg roll chicken and ice cream on community group partners in Dusun VI, Warembungan Village, Minahasa. The participants who attended were 30 people who were representatives of community groups. Food ingredients follow SNI and the water content of dry cakes is a maximum of 5%. The method used is divided into six (6) stages, namely: survey, administrative preparation, making ice cream and egg rolls in the laboratory, preparing food ingredients for activities, and implementing mentoring, and activity reports. Mentoring was carried out on August 23, 2024 with partners. The results of the mentoring have provided knowledge for partner groups so that they can sustainable produce food ingredients that are safe for the health of the community and tourists.